LncRNA OIP5-AS1 Knockdown Targets miR-183-5p/GLUL Axis and Inhibits Cell Proliferation, Migration and Metastasis in Nasopharyngeal Carcinoma - Li, Shuo; Tang, Mingxing; Zen, Nan; Liang, Junyi; Xing, Xiao; Huang, Danglin; Liu, Fei; Zhang, Xiaomeng (Frontiers in Oncology, 2022)
Nasopharyngeal carcinoma (NPC) is often associated with the infection of Epstein-Barr virus in nasopharynx and is mainly happened in South China and Southeast Asia. Recently, noncoding RNAs have been reported to regulate NPC carcinogenesis. LncRNA OIP5-AS1 participates in tumorigenesis and progression; however, the inherent mechanism of OIP5-AS1-mediated progression of NPC is unclear. In the current study, we aimed to explore the role of OIP5-AS1 in NPC progression. We measured the cell viability, apoptosis, migration, and invasion in NPC cells after OIP5-AS1 modulation. Moreover, we determined whether OIP5-AS1 exerts its oncogenic functions via sponging miR-183-5p in NPC. Furthermore, we determined whether glutamate ammonia ligase (GLUL) was a downstream target of miR-183-5p. We found that OIP5-AS1 downregulation inhibited the viability, migration and invasion of NPC via targeting miR-183-5p. We also identified that GLUL might be a potential downstream target of miR-183-5p in NPC cells. Mechanistically, OIP5-AS1 promotes cell motility via regulating miR-183-5p and GLUL in NPC cells. We concluded that OIP5-AS1 performed its biological functions via targeting miR-183-5p and GLUL in NPC cells.